THE INFLUENCE OF INTERVENTION AQUATIC WITH STUDENTS WITH INTELLECTUAL DISABILITIES PROJECT PARTICIPANTS PIRACEMA - ASSESSMENT AND CLASSIFICATION OF MOTOR DEVELOPMENT (Fiep Bulletin - online, 2014)
This search, of descriptive exploratory character, aimed to check and analyze the General Motor Age of students' participants of Piracema Project, through the Motor Development Scale. This search had the participation of 13 students enrolled on APAE and participants of project, of age between 12 and 46 years old, being 7 females and 6 males. The aspects analyzed was Fine Motricity, Global Motricity, Equilibrium, Body Scheme, Spatial Organization and Temporal Organization, comparing the tests of November of 2012 and May of 2013. From tests, the results that we obtained in relation to General Motor Age was that 70% had your ages high and 30% had a small reduction. In relation of Fine Motricity, 61,5% of students maintained their values, 30,8% high and just one student (7,7%) decreased. In the Global Motricity, of the total group, we obtained that 46,1% maintained their ages and 46,1% high, having just 7,8% decreased their values. Analyzing the battery of Equilibrium, 46,1% of students high your values, 38,5% maintained and 15,4% reduced your ages. In relation of Body Scheme, we obtained that 53,8% of students maintained their motor ages, 30,8% high and 15,4% reduced their values. From of group analyzed, on the battery of Spatial Organization, we obtained that 30,8% high your values and 30,8% maintained, having 38,5% of the students reduced their values. Lastly, the battery of Temporal Organization show that 53,8% of the students high their values, 30,8% maintained and 15,4% reduced. Based on analyzes made, we can conclude that there was an improvement in the average of all aspects analyzed.
Keywords: Motor Development; People with Intellectual Disability; Water Activities